Trends in behavior analysis in education - Sulzer-Azaroff, Beth (1990)
The preparation of the Journal of Applied Behavior Analysis Reprint Series: Behavior Analysis in Education (1988) provided an opportunity to survey and analyze trends in the field, as reflected by publications in the journal. Apparently, the large volume of behavior-analytic papers on educational topics has been declining and its contents undergoing some interesting but not uniformly welcome shifts. Although the intense concern with classroom conduct has diminished somewhat, that topic continues to be heavily emphasized. Simultaneously, reports of social skills and language studies have accelerated, but analyses of academic performance have progressively declined. Explanations for the findings remain speculative, but behavior analysts are encouraged to address these areas of essential social need.